2000
DOI: 10.1161/01.atv.20.4.1155
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Transcription of the Plasminogen Activator Inhibitor-1 Gene Through Genistein-Sensitive Tyrosine Kinase Pathways in Vascular Endothelial Cells

Abstract: Abstract-A decline in oxygen concentration perturbs endothelial function, which promotes local thrombosis. In this study, we determined whether hypoxia in the range of that observed in pathophysiological hypoxic states stimulates plasminogen activator inhibitor-1 (PAI-1) production in bovine aortic endothelial cells. PAI-1 production, measured by ELISA, was increased by 4.7-fold (PϽ0.05 versus normoxic control, nϭ4) at 12 hours after hypoxic stimulation. Northern blot analysis showed the progressive time-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 44 publications
8
60
1
Order By: Relevance
“…Cells were maintained at an oxygen concentration of 1−3% oxygen, a level similar to that which the placenta is exposed to before 10 weeks of pregnancy [32]. These results are consistent with previous studies demonstrating hypoxic induction of PAI-1 expression in trophoblasts and other cell types, and the demonstration of a HRE in the PAI-1 promoter [21][22][23]. We observed that hypoxic treatment induced a small (∼40%) but significant increase in PAI-1 levels in culture media from BeWo choriocarcinoma cells, whereas PAI-1 levels were extremely low in JAR choriocarcinoma cells under normoxic and hypoxic conditions (not shown).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cells were maintained at an oxygen concentration of 1−3% oxygen, a level similar to that which the placenta is exposed to before 10 weeks of pregnancy [32]. These results are consistent with previous studies demonstrating hypoxic induction of PAI-1 expression in trophoblasts and other cell types, and the demonstration of a HRE in the PAI-1 promoter [21][22][23]. We observed that hypoxic treatment induced a small (∼40%) but significant increase in PAI-1 levels in culture media from BeWo choriocarcinoma cells, whereas PAI-1 levels were extremely low in JAR choriocarcinoma cells under normoxic and hypoxic conditions (not shown).…”
Section: Discussionsupporting
confidence: 89%
“…Previous work showed that PAI-1 expression is increased under hypoxic conditions in several cell types including trophoblasts [21,22]. The PAI-1 gene, like several other hypoxiaresponsive genes, has a hypoxia response element (HRE) in its promoter through which hypoxia-inducible factor (HIF) induces transcription [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is just this type of approach that could open new avenues to understand myocardial disease processes in terms of mechanisms not currently considered. Examples of these genes are PAI-1 and -2, which have been described in endothelial cells and tumors (12,15,45). Because one could argue that these genes were upregulated in the heart, but not in myocytes, e.g., vessels, fibroblasts, macrophage, we needed to confirm that the up-regulation was specific to myocytes.…”
Section: Up-regulation In Stunned Myocardium Of Genes Not Previously mentioning
confidence: 99%
“…In contrast, when endothelial cells migrate, they upregulate uPA, uPAR and PAI-1 [55][56][57][58]. Hypoxia, a major stimulus for angiogenesis has been reported to increase uPAR and PAI-1 expression in endothelial cells [59]. A variety of angiogenic factors (cytokines and growth factors) control the expression of the plasminogen system.…”
Section: The Plasminogen System and Angiogenesismentioning
confidence: 99%